A kiss in the midst of a riot: community, impact and persistence - Mateo León, José Enrique (Re-visiones, 2024)
An apparent contradiction arises when, despite the shared life in community of images, one of them stands out from the rest. In June 2011, in an insistent context of photographs arising from street disturbances, one photographer achieved space on the front pages of numerous media outlets. In that image, we saw what appeared to be two young people kissing, lying in the street, surrounded by a violent situation. We will analyse the reasons, in their context, for which this image stood out from the others, and to what point the inertia of the reiterated visual offering extends.